Inhibition of Follicle-Stimulating Hormone-Induced Preovulatory Follicles in Rats Treated with a Nonsteroidal Negative Allosteric Modulator of Follicle-Stimulating Hormone Receptor. Issue 1 (1st January 2014) - Dias, James A.; Campo, Brice; Weaver, Barbara A.; Watts, Julie; Kluetzman, Kerri; Thomas, Richard M.; Bonnet, Béatrice; Mutel, Vincent; Poli, Sonia M.
Abstract: We previously described a negative allosteric modulator (NAM) of FSHR (ADX61623) that blocked FSH-induced cAMP and progesterone production but did not block estradiol production. That FSHR NAM did not affect FSH-induced preovulatory follicle development as evidenced by the lack of an effect on the number of FSH-dependent oocytes found in the ampullae following ovulation with hCG. A goal is the development of a nonsteroidal contraceptive. Toward this end, a high-throughput screen using human FSHR identified an additional nonsteroidal small molecule (ADX68692). Although ADX68692 behaved like ADX61623 in inhibiting production of cAMP and progesterone, it also inhibited FSH-induced estradiol in an in vitro rat granulosa primary cell culture bioassay. When immature, noncycling female rats were injected subcutaneously or by oral dosing prior to exogenous FSH administration, it was found that ADX68692 decreased the number of oocytes recovered from the ampullae. The estrous cycles of mature female rats were disrupted by administration by oral gavage of 25 mg/kg and 10 mg/kg ADX68692. In the highest dose tested (25 mg/kg), 55% of animals cohabited with mature males had implantation sites compared to 33% in the 10 mg/kg group and 77% in the control group. A surprising finding was that a structural analog ADX68693, while effectively blocking progesterone production with similar efficacy as ADX68692, did not block estrogen production and despite better oral availability did not decrease the number of oocytes found in the ampullae even when used at 100 mg/kg. These data demonstrate that because of biased antagonism of the FSHR, nonsteroidal contraception requires that both arms of the FSHR steroidogenic pathway must be effectively blocked, particularly estrogen biosynthesis. Thus, a corollary to these findings is that it seems reasonable to propose that the estrogen-dependent diseases such as endometriosis may benefit from inhibition of FSH action at the ovary using the FSHR NAM approach.